2012
DOI: 10.1038/jhg.2012.12
|View full text |Cite
|
Sign up to set email alerts
|

Association analysis of formyl peptide receptor 2 (FPR2) polymorphisms and Aspirin exacerbated respiratory diseases

Abstract: Aspirin-exacerbated respiratory diseases (AERD) are associated with the metabolism of arachidonic acid. FPR2 (formyl peptide receptor2) is a high-affinity ligand receptor for potent anti-inflammatory lipid metabolites: lipoxins. Thus, functional alterations of the FPR2 may contribute to AERD. We investigated the relationship between single-nucleotide polymorphisms (SNPs) in the FPR2 and AERD. Asthmatics were categorized into AERD o15% decreases in forced expiratory volume in one second (FEV 1 ), and/or naso-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Taken together, the three SNPs (rs11666254, rs17695052, and rs17695064) selected in this study for genotyping might capture most of the genetic variation of the entire FPR2/ALX gene and might represent potential biological significance of the FPR2/ALX genetic variations. Three SNPs in our study (rs11666254 [−1010G/A], rs7248161 [−1160G/G], and rs7256993 [398 T/T]) were not included in Kim et al’s study [37]. The reason may be the relatively low MAF of the three SNPs in their study population.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Taken together, the three SNPs (rs11666254, rs17695052, and rs17695064) selected in this study for genotyping might capture most of the genetic variation of the entire FPR2/ALX gene and might represent potential biological significance of the FPR2/ALX genetic variations. Three SNPs in our study (rs11666254 [−1010G/A], rs7248161 [−1160G/G], and rs7256993 [398 T/T]) were not included in Kim et al’s study [37]. The reason may be the relatively low MAF of the three SNPs in their study population.…”
Section: Discussionmentioning
confidence: 95%
“…Gwinn et al found that two SNPs (F110S and C126W), which were located in the open reading frame of FPR2/ALX , were associated with juvenile periodontitis [36]. Kim et al observed that an intronic SNP (4209 T/G) was associated with the risk of asthma disease [37]. These three SNPs (F110S and C126W, 4209 T/G) along with 220A/G variants (data in the study by Simiele et al [29]) were not analyzed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Functional N-acetyltransferase and CYP2C polymorphisms have recently been analyzed in relation to metamizole metabolic profile [85 && ]. Associations with NERD have been also reported for SNPs in formyl peptide receptor 2, a high-affinity ligand receptor for lipoxins [86], heat shock protein 70 [87], and members of the rat sarcoma viral (RAS) oncogene family [88].…”
Section: Miscellaneous Associationsmentioning
confidence: 90%
“…The fact that PSM levels correspond to staphylococcal virulence 74 suggests that PSMs are true PAMPs that enable the innate immune system to initiate appropriate immune responses via FPR2. Mast cell degranulation can be elicited by δ-toxin, an α-type PSM 83 , and polymorphisms in FPR2 are associated with urticaria 84 and asthma 85,86 , which suggests that PSM-FPR2 interactions may also be important co-triggers of allergies. who are hospitalized and immunocompromised 87 .…”
Section: Staphylococcal Psmsmentioning
confidence: 99%